Intonation structuring of coherent Tuvan folklore narration - Ryzhikova, Tatiana R.; Dobrinina, Albina A.; Plotnikov, Ilya M.; Shestera, Elena A.; Shamrin, Anton S. (The New Research of Tuva, 2021)
The article presents preliminary data on the intonation of the Tuvan folklore narration with specific focus to the relation between intonation and text structure. The analysis was carried out on the basis of four Tuvan folklore texts. Three hypothetical intonational correlates of the text structure were examined. First, we consider the difference in tempo of the main parts of the texts, following the idea of three-part structure of folklore texts proposed by V. Propp (beginning, complication and ending). The data obtained show no direct correspondence between the tempo of an utterance and its position in the text, as the tempo of the first and the last utterances and their ratio to the average tempo vary significantly from text to text. Secondly, it is shown that the texts contain a number of metatext markers, which are used quite often and are distinguished by the means of intonation (including changes in tone and intensity and separation by a pause). Thirdly, verbal forms with particle -tyr performing similar functions are examined. In contrast to metatext markers, they are not characterized by any intonational prominence, as the tone and intensity follow the general line of declination marking the end of an utterance. Thus, intonation plays an important role in forming the structure of Tuvan folklore texts, which, however, manifests itself only indirectly, in the way of emphasizing lexical means of structuring the text (metatext markers).
Keywords: intonation; syntax; metatext markers; Tuvan language; folklore; narrative tradition; Tuvan folklore